Remnant cholesterol, stronger than triglycerides, is associated with incident non-alcoholic fatty liver disease - Cheng, Yiping; Zhang, Qiang; Li, Haizhen; Zhou, Guangshuai; Shi, Ping; Zhang, Xu; Guan, Liying; Yan, Fang; Xu, Chao (Frontiers in Endocrinology, 2023)
Non-alcoholic fatty liver disease (NAFLD) is characterized by excess accumulation of triglycerides within the liver. However, whether the circulating levels of triglycerides and cholesterol transported in triglyceride-rich lipoproteins (remnant cholesterol, remnant-C) are related to the occurrence of NAFLD has not yet been studied. This study aims to assess the association of triglycerides and remnant-C with NAFLD in a Chinese cohort of middle aged and elderly individuals. In multivariable-adjusted Cox proportional hazard model analyses, triglycerides (hazard ratio[HR], 95% confidence interval [CI]: 1.080, 1.047-1.113;p＜0.001), high-density lipoprotein cholesterol (HDL-C) (HR, 95% CI: 0.571,0.487-0.670; p＜0.001), and remnant-C (HR, 95% CI: 1.143,1.052-1.242; p=0.002), but not total cholesterol (TC) or low-density lipoprotein cholesterol (LDL-C), were associated with incident NAFLD. Atherogenic dyslipidemia (triglycerides>1.69 mmol/L, HDL-C<1.03 mmol/L in men or<1.29 mmol/L in women) was also associated with NAFLD (HR, 95% CI: 1.343,1.177-1.533; p＜0.001). Remnant C levels were higher in females than in males and increased with increasing BMI and in participants with diabetes and cardiovascular disease (CVD) compared with those without diabetes or CVD. After adjusting for other factors in the Cox regression models, we found that serum levels of TG and remnant-C, but not TC or LDL-C, were associated with NAFLD outcomes in women group, non-cardiovascular disease status, non-diabetes status and middle BMI categories (24 to 28 kg/m2). In the middle aged and elderly subset of the Chinese population, especially those who were women, non-cardiovascular disease status, non-diabetes status and middle BMI status (24 to 28 kg/m2), levels of triglycerides and remnant-C, but not TC or LDL-C, were associated with NAFLD outcomes independent of other risk factors.